AS LIMITAÇÕES DO SILOGISMO LÓGICO-DEDUTIVO E DO RECURSO À SUBSUNÇÃO NA ARGUMENTAÇÃO JURÍDICA (Revista Paradigma, 2025)
ABSTRACT: This paper aims to show the limits of the use of logical-deductive syllogism and subsumption as unrestrictedly valid legal arguments. It addresses the insufficiency of the criterion of logical formal validity to guarantee the veracity of the premises; and focuses law’s need to be concerned with the content justifications of the argument. The article deals with the limiting task of the premises, the dependence on linguistic conventions, the submission to rules of evidence and to interpretative reasoning, the adversarial character of the judicial process. It also considers analogy and balancing as two basic operations of law, besides subsumption. The article also exposes how reasoning formalizations built from logical-deductive chains may carry an expectation of completeness of the legal order and of the judge’s rationality, hiding the complexity of the legal phenomenon and the decision-making process.